The Marauders - Ogburn, Charlton (New York Ballantine Books, 1974)
The classic WW II account of Merrill's Marauders -- The Now Legendary Fighting Units Left Behind in the Jungles of Burma.
English Fiction.
Keywords: United States. Army. Composite Unit (Provisional), 5307th -- World War (1939-1945) -- Burma